2020
DOI: 10.1111/1744-7917.12775
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of pheromone receptor candidates in codling moth Cydia pomonella (Lepidoptera: Tortricidae)

Abstract: Sex pheromones serve a critical role in Lepidopterans finding mates. Male moths perceive and react to sex pheromones emitted by conspecific females through a delicate pheromone communication system. Pheromone receptors (PRs) are the key sensory elements at the beginning of that process. The codling moth (Cydia pomnonella) is an important pome fruit pest globally and a serious invasive species in China. Pheromonebased techniques have been used successfully in monitoring and controlling this species. We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 58 publications
(85 reference statements)
1
13
0
Order By: Relevance
“…The results of RTq-PCR analysis show that PflaOR21, PflaOR27, PflaOR29, PflaOR35, PflaOR37, PflaOR40, PflaOR42, PflaOR44, PflaOR60, and PflaOR62 have sex-biased expression in male antennae and may be involved as specificity-sensing sex pheromone compound. These results are similar to those of CpomPRs (i.e., CpomOR1, CpomOR2a, CpomOR5, and CpomOR7) in C. pomonella, in which CpomOR2a and CpomOR5 respond to an important component of C. pomonella sex pheromone (Tian et al, 2021). Classical (i.e., PflaOR27, PflaOR29, PflaOR44, PflaOR60, and PflaOR62) and novel (i.e., PflaOR21, PflaOR35, PflaOR37, PflaOR40, and PflaOR42) PR clades show male sex-biased expression in the antennae.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results of RTq-PCR analysis show that PflaOR21, PflaOR27, PflaOR29, PflaOR35, PflaOR37, PflaOR40, PflaOR42, PflaOR44, PflaOR60, and PflaOR62 have sex-biased expression in male antennae and may be involved as specificity-sensing sex pheromone compound. These results are similar to those of CpomPRs (i.e., CpomOR1, CpomOR2a, CpomOR5, and CpomOR7) in C. pomonella, in which CpomOR2a and CpomOR5 respond to an important component of C. pomonella sex pheromone (Tian et al, 2021). Classical (i.e., PflaOR27, PflaOR29, PflaOR44, PflaOR60, and PflaOR62) and novel (i.e., PflaOR21, PflaOR35, PflaOR37, PflaOR40, and PflaOR42) PR clades show male sex-biased expression in the antennae.…”
Section: Discussionsupporting
confidence: 81%
“…Among the receptor proteins, PRs are a special type of OR that participate in pheromone reception (Wu et al, 2022). Therefore, extensive studies have been conducted on its identification and function in insect pests for potential control (Tian et al, 2021), including BmOR1 and BmOR2 of B. mori (Sakurai et al, 2004;Nakagawa et al, 2005);HR13, HR14, and HR16 of H. virescens (Grosse-Wilde et al, 2007); and PxOR1, MsOR1, and DiOR1 of Plutella xylostella, Mythimna separata, and Diaphania indica, respectively (Mitsuno et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…External chemical signals are detected by odorant receptors (ORs), gustatory receptors (GRs), and ionotropic receptors (IRs) on the dendritic membrane of these OSNs, and are converted into electrical signals and transmitted to the brain (Leal, 2013; Fleischer et al ., 2018). ORs are mainly in response to plant volatiles and sex pheromones, which contain messages pertaining to food, alarms, and mates (Leal, 2013; Cao et al ., 2016; Chang et al ., 2017; Cui et al ., 2018; Fleischer et al ., 2018; Liu et al ., 2018; Zhang et al ., 2019a; Cao et al ., 2020; Chen et al ., 2020; Guo et al ., 2020; Li et al ., 2020; Tian et al ., 2021). For instance, males have pheromone receptors to detect sex pheromones released by females for mating.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2016. Phylogenetic analysis constructed with 10 SPRs from Cydia fagiglandana, 7 SPRs from Hedya nubiferana, 8 SPRs from B. mori, 6 SPRs from E. postvittana, and 14 SPRs from C. pomonella revealed that the four genes (i.e., CpomOR1, CpomOR2a, CpomOR5, and CpomOR7) were clustered with Lepidopteran SPRs (Tian et al, 2020). In the phylogenetic tree of SPR subfamily proteins, OR1/3/4/5/6/7/8 of different Ostrinia species, respectively, formed a clade (Miura et al, 2010).…”
Section: Evolution Of Lepidopteran Sex Pheromone Receptorsmentioning
confidence: 99%
“…The two-electrode voltage-clamp recording was conducted in Xenopus oocytes coinjected with complementary RNAs encoding BmOR1 and BmOR2 to test the bombykolinducing current response (Nakagawa et al, 2005). The similar method was used in a specific pheromone detection of PxylOR1/4/8/41/45 (Sun et al, 2013;Liu et al, 2018), MsexOR1 (Wicher et al, 2017), EgirOR1 (Li et al, 2017), MsepOR2/3 (Jiang et al, 2019(Jiang et al, , 2020, HvirOR6/13/14/16 (Wang et al, 2011), SexiOR13/16 , SinfOR21/29 (Zhang et al, 2014), AlepOR3/4/6 (Zhang et al, 2019), HarmORs/HassORs Liu et al, 2014;Jiang et al, 2014;Xu et al, 2015), AsegOR1/4/5/6/9 (Zhang and Lofstedt, 2013), SlituOR6/13/16 (Zhang et al, 2015), CpomOR2a/5 (Tian et al, 2020), AtraOR1/3 (Xu et al, 2012), and OlatOR1/OovaOR1/OscaOR1/3/4/5 (Miura et al, 2009(Miura et al, , 2010. HEK293/sf9 cell calcium assay verified the sex pheromone component of ApolOR1, HassOR13, CoblOR7, and CherOR7 (Forstner et al, 2009;Jordan et al, 2009;Liu et al, 2014;Steinwender et al, 2015;Xu et al, 2015).…”
Section: Characterization and Interaction Of Sex Pheromone Receptors ...mentioning
confidence: 99%